Isolated brainstem involvement in posterior reversible encephalopathy syndrome: a case report and review of the literature. (3rd August 2019) - Liu, Chenchen; Cao, Jie; Su, Zhuyi; Xu, Shabei
Abstract: Posterior reversible encephalopathy syndrome (PRES) is a clinical–radiological syndrome, reversible vasogenic edema predominantly within parieto-occipital regions. However, isolated brainstem involvement in PRES has been rarely reported, little is known about its clinical manifestations, radiological features and outcomes. We reported a case with PRES with only brainstem involvement and performed a systematic review of published cases. Twenty-four cases, together with our case, were included in the analysis. Mean age was 43 years and 63% were males. Hypertension (50%), nephropathy (25%) and chemotherapy (21%) were the major risk factors. All patients except two had acute hypertension and 50% of patients had renal dysfunction at onset. The most common symptoms were altered consciousness (46%) and headache (46%), Seizure was only presented in 21% of patients. All patients except two were treated with antihypertension. Most patients recovered to their neurological baseline. Clinicians should recognize this unique variant finding in PRES. which always affects males with severe hypertension, especially combined with renal dysfunction. Antihypertensive treatment is the most widely used therapy. Outcome is usually well.